Racial Inequality in Organizations: A Systems Psychodynamic Perspective - Mobasseri, Sanaz; Kahn, William A.; Ely, Robin J. (Academy of Management Review, 2024)
This paper uses systems psychodynamic concepts to develop theory about the persistence of racial inequality in U.S. organizations and to inform an approach for disrupting it. We treat White men as the dominant group and Black people as the archetypal subordinate group in U.S. society. In our theory, work contexts that conflate merit with idealized images of White masculinity provoke unconscious distress in White men who aspire to meet those ideals. An unconscious, multilevel defense system, comprising projective identification at the individual level bolstered by a social defense at the organization level, keeps this distress at bay. This system diverts attention away from the real culprit—work contexts that threaten White men’s self-worth—by contriving and making credible a substitute problem—a shortage of “qualified” Black people. At the same time, the social defense fuels the very work contexts that pose threats to White men in the first place. The upshot is the persistence of racial inequality. We offer guidance on how to disrupt these dynamics by building mutually reinforcing holding environments where organization members can engage in intrapsychic and intergroup reparative work. We conclude by offering theoretical contributions to the literatures on race, organizational inequality, systems psychodynamics, and masculinity.